Evaluation of two commercially available ELISAs for the diagnosis of Japanese encephalitis applied to field samples - Lewthwaite, Penny; Shankar, M. Veera; Tio, Phaik-Hooi; Janet, Daly; Anna, Last; Ravikumar, R.; Anita, Desai; Ravi, V.; Mary Jane, Cardosa; Tom, Solomon (John Wiley & Sons Ltd, 2010)
To compare two commercially available kits, Japanese Encephalitis-Dengue IgM Combo ELISA (Panbio Diagnostics) and JEV-CheX IgM capture ELISA (XCyton Diagnostics Limited), to a reference standard (Universiti Malaysia Sarawak – Venture Technologies VT ELISA). Methods Samples were obtained from 172 ⁄ 192 children presenting to a site in rural India with acute encephalitis syndrome.